The Influence of Job Insecurity on Turnover Intention Through Employee Job Stress as a Mediation Variable at PT Sarana Pembangunan Pekanbaru (Trans Metro Pekanbaru) - Anuar, Saiful; Moein, Anoesyirwan; Zami, Alex (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to examine the effect of job insecurity on turnover intention through employee work stress as a mediating variable. The sample was selected using the purpose sampling method, namely judgment sampling and data was collected through distributing questionnaires. The sample chosen was employees of Trans Metro Pekanbaru (PT Sarana Pembangunan Pekanbaru). The number of observations used was 63 employees. Sample data was tested using Path Analysis with the help of SmartPLS 3.0. The test results show that there is a positive but not significant influence between job insecurity on turnover intention, while job insecurity has a positive and significant influence on work stress. Then, there is a positive and significant influence between the relationship between work stress and turnover intention.